From tolerance work to pedagogies of unease: affective investments in Danish antiracist education - Mante Vertelyte; Dorthe Staunæs (Taylor & Francis Group, 2021)
Antiracist pedagogies have long been conceptualized and developed by scholars, public intellectuals, teachers and pedagogues in Danish education contexts. By analysing Danish knowledge production on antiracist education from the 1980s to the present, this article traces changing understandings of race and racism in Danish education, as well as accounts for different affective tensions and investments at stake in antiracist pedagogical practice and thinking. We show how the discourse of antiracism as 'tolerance work' prevalent in the 1980s and 1990s evolved into an antiracist pedagogy centred on 'creating good and positive atmospheres', and how, from the 2000s onward, feelings of unease, embarrassment and anxiety about addressing race have become integrated in antiracist education research and practice. While the first approach towards antiracist education dwells with and use positive and joyous feelings, the second wave addresses a more uncomfortable register of affects. By analysing how different affective intensities have historically been associated with antiracist pedagogies in Denmark, we show how they are inextricable from education policies and politics.